A critical SiOx layer on Si porous structures to construct highly-reversible anode materials for lithium-ion batteries. Issue 45 (22nd May 2017) - Chen, Yifan; Lin, Yangfan; Du, Ning; Zhang, Yaguang; Zhang, Hui; Yang, Deren
Abstract : A novel Si/SiO x porous structure with an ∼9 nm SiO x coating layer demonstrates a highly reversible discharge capacity of over 915 mA h g −1 after 500 long cycles. Abstract : A novel Si/SiO x porous structure with a SiO x coating layer of varying thicknesses was prepared via a simple annealing and acid washing process. When used as an anode material for lithium-ion batteries, the Si/SiO x porous structure with an ∼9 nm SiO x coating layer demonstrates significantly improved electrochemical performance with a high reversible discharge capacity of over 915 mA h g −1 after 500 long cycles at 1 A g −1 . The lithiation mechanism of a SiO x layer of different thicknesses has also been investigated.